Reformulating the Concept of Ihdad in the Contemporary Era: A Review of the Concept of Ihdad According to Jurisprudence Scholars - Yuliantari, Ela; Azwar, Zainal (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The importance of a more contextual understanding of Ihdad (the mourning period for women after the death of their husbands) is emphasized, considering the ongoing social and cultural changes. Although it has strong roots in Islamic law and has been widely discussed by ulama, its application in contemporary era requires a more relevant approach that aligns with the conditions of modern society while maintaining the essence of the underlying teachings. This research aims to revisit the concept of Ihdad from a jurisprudential perspective and to explore the possibility of its adaptation to remain in harmony with the needs and realities of today’s Muslim women. The methodology used is a literature study, collecting data from books, journals, and scientific articles, which is then explained descriptively. The findings indicate that, first, ulama have differing views on Ihdad, yet they all mandate it under specific conditions for the well-being of widowed wives. Second, regarding Ihdad in contemporary era, it is explained that Islamic traditions have been adopted by Muslims since the time of Prophet Muhammad. From the first week of life to the present, they have been characterized by a strong sense of dignity, even if it requires traditional forms. This research contributes to providing a more inclusive and relevant understanding of Ihdad as part of the dynamics of jurisprudence and the lives of modern Muslim women.